Dimensions Of Classroom Interaction In The Use Of Digital Media - Stadermann, Melanie; Schulz-Zander, Renate (MediaEducation: Journal for Theory and Practice of Media Education, 2012)
The use of digital media in the classroom, in addition to promoting media literacy and subject-specific skills, aims to promote generic skills in the areas of self-direction, cooperation, communication and problem solving as a prerequisite for lifelong learning and preparation for the world of work. In essence, these skills belong to the key competences of the 21st century. Digital media are seen as playing an important role in knowledge construction, changing the learning culture and improving the quality of teaching and schools.